THE ROLE AND PLACE OF THE PRAGMATIC VALUE IN THE SEMANTIC STRUCTURE OF THE WORD - Tairova Dilnoza Adil qizi (Journal of new century innovations, 2023)
Abstract: Pragmatics or pragmalinguistics, one of the stages of linguistics, rich in new and topical problems, is characterized by a communicative approach to language. This means that language is seen as a means of communication, and the communicative function of language is recognized as its main function. Communicative linguistics studies language activity as a speech activity as a language of use.